Addressing Competitive Responses to Acquisitions. (May 2016) - King, David R.; Schriber, Svante
Competitive retaliation is a significant constraint to merger and acquisition performance that has largely been overlooked by management research. This article employs competitive dynamics theory to explore how acquisition characteristics impact the risk of competitor retaliation. It then outlines different tactics that acquiring firms can use to reduce competitor awareness, motivation, and capability associated with retaliation. It provides managers with a path to improving acquisition performance and also opens new avenues for research.